Pendidikan Islam Dan Tantangan Modernitas (Input, Proses Dan Output Pendidikan Di Madrasah) - Muhammad Anas Ma`arif (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2016)
Discussing education is never finished, there is always something new in the world of education. Education today has the challenge of modernity that makes education must innovate even more Islamic education. Education is not just looking for input is good for the process be graduates (output) is good but how a quality process that makes the product (graduates) were good. Therefore, to answer the challenges of modernity, education must have a strategy to develop education as an input, education as a process and education as a superior product.